Earth's ion upflow associated with polar cap patches: Global and in situ observations. Issue 5 (8th March 2016) - Zhang, Qing‐He; Zong, Qiu‐Gang; Lockwood, Michael; Heelis, Roderick A.; Hairston, Marc; Liang, Jun; McCrea, Ian; Zhang, Bei‐Chen; Moen, Jøran; Zhang, Shun‐Rong; Zhang, Yong‐Liang; Ruohoniemi, J. Michael; et al.
Abstract: We report simultaneous global monitoring of a patch of ionization and in situ observation of ion upflow at the center of the polar cap region during a geomagnetic storm. Our observations indicate strong fluxes of upwelling O + ions originating from frictional heating produced by rapid antisunward flow of the plasma patch. The statistical results from the crossings of the central polar cap region by Defense Meteorological Satellite Program F16–F18 from 2010 to 2013 confirm that the field‐aligned flow can turn upward when rapid antisunward flows appear, with consequent significant frictional heating of the ions, which overcomes the gravity effect. We suggest that such rapidly moving patches can provide an important source of upwelling ions in a region where downward flows are usually expected. These observations give new insight into the processes of ionosphere‐magnetosphere coupling. Key Points: First simultaneous global monitoring of patch and in situ observation of ion upflow in the polar cap Strong fluxes of upwelling O + originating from frictional heating produced by rapid flow of patch Rapidly moving patches can provide an important source of upwelling ions